2019
DOI: 10.24251/hicss.2019.350
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Governance Approach to Partnerships Addressing Public Problems with Private Data

Abstract: The recent explosion of data, which is generated, collected, and exchanged, opens up new opportunities and poses new challenges. Actors in different sectors have recently began to explore how they can work together and leverage these data to help address 'wicked' problems. A novel form of cross sector partnership emerges, labelled "data collaborative", which is normally focused on accessing private sector data and using it to address complex public problems. While there is emerging knowledge about how data can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…Gil-Garcia (2012) thus proposed that governments can gain additional benefits if they engage in information sharing initiatives across various levels of government, with governments from different countries, multiple branches of government, non-for-profit organisations, and businesses. Recent research on data collaboratives echoes further these ideas (Susha & Gil-Garcia, 2019;Susha, Jannsen, & Verhulst, 2017;Verhulst & Sangokoya, 2015;Verhulst, Young, & Srinivasan, 2017).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Gil-Garcia (2012) thus proposed that governments can gain additional benefits if they engage in information sharing initiatives across various levels of government, with governments from different countries, multiple branches of government, non-for-profit organisations, and businesses. Recent research on data collaboratives echoes further these ideas (Susha & Gil-Garcia, 2019;Susha, Jannsen, & Verhulst, 2017;Verhulst & Sangokoya, 2015;Verhulst, Young, & Srinivasan, 2017).…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, business information from documents, such as purchase orders, invoices, packing lists), is commercially sensitive, so companies are reluctant to share it with other parties than those that are directly involved in their commercial operations. Therefore, voluntary information sharing is extremely challenging and relies heavily on articulating benefits and finding the right incentives for all parties involved (Gascó, Feng, & Gil-Garcia, 2018;Susha & Gil-Garcia, 2019). Another major challenge relates to governance (Emerson, Nabatchi, & Balogh, 2012;Rukanova, Henningsson, Henriksen, & Tan, 2018;Susha & Gil-Garcia, 2019) since voluntary information sharing arrangements involve a complex network of business and government actors which have their own interests, but need to engage in a process and work together to achieve the voluntary sharing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These intermediation concepts provide the necessary depth for conceptualizing and grounding the notion of intermediaries of data collaboratives in existing academic research. Previous research [30] found that, compared to collaborations in general, data collaboratives face very specific collaboration challenges: the decisive role of trust between parties, data stewardship, data-related risk mitigation, and formulating value proposition to both sides. Intermediaries of data collaboratives, therefore, have a potential to create value by addressing these challenges.…”
Section: Intermediaries In Data Collaboratives: Conceptualizationmentioning
confidence: 99%
“…When it comes to interorganizational information sharing (IIS) research, there are distinct differences as well: in contrast to IIS which has focused on government-to-government sharing, data collaboratives attempt to use not only public but especially previously closed private data to address important social problems. They do not integrate all their data in a permanent system but take advantage of the availability of diverse and complementary public and private data to better understand a specific problem and propose a solution (Susha & Gil-Garcia, 2019).…”
Section: Successful Data Collaboratives: Literature Reviewmentioning
confidence: 99%